Implementasi Metode Demonstrasi dalam Pembelajaran Tata Cara Sholat di Madrasah Ibtidaiyah (MI) Manba’ul Ilmin Nafi’ Gunungmulyo Sarang - Koifatul Ainiah; Sholahuddin Fatawi (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2025)
Learning the procedures of prayer is an essential part of Islamic Religious Education in Madrasah Ibtidaiyah because prayer is an obligatory worship that must be understood and practiced from an early age. However, in practice, some students still have difficulties in understanding the correct movements and recitations of prayer. This study aims to describe the implementation of the demonstration method in teaching prayer procedures at Madrasah Ibtidaiyah, students’ responses to the method, and the supporting and inhibiting factors. This research employed a descriptive qualitative approach using observation, interviews, and documentation as data collection techniques. The research subjects were Islamic Religious Education teachers and students of Madrasah Ibtidaiyah. The results show that the demonstration method was implemented through preparation, implementation, and evaluation stages. This method increased students’ activeness, enthusiasm, and understanding of prayer procedures. Supporting factors included teacher readiness and facilities, while inhibiting factors were limited learning time and differences in students’ abilities.